2020
DOI: 10.3389/fmicb.2020.01897
|View full text |Cite
|
Sign up to set email alerts
|

A Shallow Water Ferrous-Hulled Shipwreck Reveals a Distinct Microbial Community

Abstract: Shipwrecks act as artificial reefs and provide a solid surface in aquatic systems for many different forms of life to attach to, especially microbial communities, making them a hotspot of biogeochemical cycling. Depending on the microbial community and surrounding environment, they may either contribute to the wreck's preservation or deterioration. Even within a single wreck, preservation and deterioration processes may vary, suggesting that the microbial community may also vary. This study aimed to identify t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 70 publications
0
7
0
Order By: Relevance
“…Phycisphaerae, Verrucomicrobia and Bacteroidetes were reported by Price et al (2020) to be at a higher abundance on shipwreck samples compared to sediment. In this study, the abundance of Verrucomicrobia and Bacteroidetes are also generally higher on the shipwreck steel (Supplementary Figure S4).…”
Section: Steel Shipwreck Microbiome Shows a Selection Of Corrodersmentioning
confidence: 98%
See 3 more Smart Citations
“…Phycisphaerae, Verrucomicrobia and Bacteroidetes were reported by Price et al (2020) to be at a higher abundance on shipwreck samples compared to sediment. In this study, the abundance of Verrucomicrobia and Bacteroidetes are also generally higher on the shipwreck steel (Supplementary Figure S4).…”
Section: Steel Shipwreck Microbiome Shows a Selection Of Corrodersmentioning
confidence: 98%
“…As solid heterogeneous substrates, shipwrecks are rapidly colonized by microorganisms which allow other organisms to attach and form an assemblage with dynamic community interactions (Price et al, 2020). A recent study on historic (sunk >50 years ago) shipwrecks in shallow water performed by (Price et al, 2020) has shown that the hull microbiome composition differs even on the phylum level compared to the closesurrounding sediments. Another recent study, performed by Hamdan et al (2018), showed a similar result in deep water.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Corrosion tubercles are often associated with MIC and microbial activities where shown to be a driving force of tubercle formation (Jin et al, 2015). Formation of tubercles have been reported from different environments but only few studies exist from natural freshwater sites (Odokuma, 2012; Phan et al, 2020; Price et al, 2020; Ray et al, 2010b). Several studies investigated the morphology and the mineral composition of these tubercles (Albahri et al, 2019; Ray et al, 2010b; Sarin et al, 2001).…”
Section: Introductionmentioning
confidence: 99%